Toward an islamic reformation civil liberties, human rights, and international law - An-Naim, Abdullahi Ahmed (ZI Publications Sdn.Bhd, 2017)
Drawing upon the teachings and writings of the Sudanese reformer, Mahmoud Mohamed Taha, this study aims to provide the intellectual foundations for a total reinterpretation of the nature and meaning of Islamic public law